Design and Research of a Variable Ratio Transmission Mechanism of Electric Power Steering System - Xueyun Li; Shuang Liang (Jixie chuandong)
The efficiency of the electric power steering system with constant ratio of differential gear train power transmission system is low transmission and physical consumption of driver is large when there is no motor power assist. In order to solve the problem， a variable ratio differential gear train power transmission system is proposed. Firstly， the reason of low transfer efficiency of the differential gear train power transmission system is analyzed by the dynamics model， and the system design scheme is put forward. Then a continuously differentiable curve function of variable transmission ratio is designed， and the noncircular gear in the system is designed. Finally， the improved scheme is analyzed by establishing mathematical model， and the physical consumption of driver is calculated. The results show that the physical consumption of driver is reduced by 9.15% after the improved scheme， which proves the rationality and effectiveness of the improved scheme.